On the analysis of muscle-actuated manipulators - Galhano, Alexandra (2019)
In previous studies a statistical method for the analysis and design of robot manipulators was developed. The new formalism revealed the limitations od standard joint-actuated mechanical manipulators. Steming from those results, in this paper we apply the new modelling concepts on the study of biological arms. The superior performances of muscle-actuated arms over standard joint-actuated manipulators are clearly demosntrated. Therefore, the resultes are a step towards the design of a new mechanical robotic structures, with performances close to the biological systems.